Chitin and chitosan extraction from edible insects : characterization and comparison between different species and by-products - Navarro, Pedro (2022)
The main goals of this work were to extract chitin and sinthetize chitosan from two different edible insect species - Tenebrio molitor larvae (TM) and Acheta domesticus (AD) as well as from by-products from A. domesticus processing (wings and legs-AD_WL).